Augmented Reality-Based Dance Training System: A Study of Its Acceptance - Iqbal J.; Sidhu M.S. (Springer Science and Business Media Deutschland GmbH, 2023)
Augmented reality; Blending; Mobile telecommunication systems; Dance training systems; Digital information; Information flow model; Interactive feedback; Learning and training; Real-world scenario; Technology acceptance model; Training sessions; Learning systems